Pekalongan Folklore `Dewi Lanjar` for Teaching Learning: A Feminist Study - Dwi Ario Fajar (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
Folklore has important role as the part of society and education. Folklore as local wisdom can be used for teaching current issues of society, such as gender issues. The objective of the study aims to analyze the Pekalongan Folklore DewiLanjar as the local wisdom from feminist perspective. This study uses descriptive qualitative method and feminism theory. The findings of this study are Dewilanjar folklore has bias gender in presenting her character, action and role. It is caused by the domination of patriarchy systems. The teacher should give the understanding to the students of the gender bias so that students can understand and tolerance to gender issues.